An evaluation of the influence of gingival display level in the smile esthetics - Suzuki, Larissa; Machado, André Wilson [UNESP]; Bittencourt, Marcos Alan Vieira (My University, 2011)
Objective: The aim of this study was to evaluate the influence of the amount of gingival display on smile esthetics. Methods: Two extraoral photographs were used: One of the close-up smile and one frontal view of the smiling face of four individuals (one Caucasian and one Afro-Brazilian man, and one Caucasian and one Afro-Brazilian woman). The photographs were manipulated in a computer and five images were created for each original photograph with different degrees of gingival display: 0 mm, 1 mm, 3 mm, 5 mm and 7 mm. Then the images were evaluated by 60 individuals who assigned a score from zero to ten to each image on a visual analogue scale. Results and Conclusions: Statistical analysis and results showed that levels of gingival display equivalent to 0 mm and 1 mm received the highest mean scores, i.e., 6.6 and 6.2, respectively, and showed no statistical difference between them (p>0.05). Gingival displays of 3 mm, 5 mm and 7 mm received lower, decreasing scores of 5.0, 3.5 and 2.9, respectively, without any statistical difference between levels 5 mm and 7 mm (p>0.05). Furthermore, the use of close-up photographs of the smile or frontal view photographs of the smiling face showed no statistical difference (p>0.05).
Keywords: Esthetic dentistry; Gingiva; Orthodontics; Smile